HISTORIOGRAFI ETNIS ARAB DI INDONESIA - Miftachul Taubah (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2022)
This paper is a literature review that discusses Arab Ethnic Historiography in Indonesia and its relation to the spread of Islam in Indonesia. By using a literature review in the form of reference books to support the data in this paper. Based on the data obtained, the arrival of ethnic Arabs in Indonesia is divided into three waves, namely: 1) 9-11 AD, namely the arrival of Sayyid Ali bin Muhammad Dibaj bin Ja'far Sadiq, who is one of the Ba'alwiy Ulama from the SyihÄb clan in Siak . 2) Century 12-15 AD, this period is famous for the arrival of Wali Songo in the archipelago. 3) The 17-19 century AD, namely the arrival of non-Habaib majority Arabs called Ghabili or Qabail who had more socio-economic purposes in addition to religion.